Intraorbital foreign body – diagnostic and therapeutic challenges - Orzechowska-Wylęgała, Bogusława; Puszczewicz, Zbigniew; Łyko-Morawska, Dorota; Niedzielska, Iwona (Klinika Oczna / Acta Ophthalmologica Polonica, 2017)
Here we report the case of a wooden intraorbital foreign body penetrated into the infratemporal fossa in a 17-year-old patient and associated diagnostic difficulties. The superiority of computed tomography over the remaining imaging examinations was proved. It was demonstrated that a patient after orbital trauma should be immediately referred to a multidisciplinary centre where radiologists liaise with oral and maxillofacial surgeons and ophthalmologists.